The mitigation pillar of Climate-Smart Agriculture (CSA): targets and options - Wollenberg, Eva Karoline (2017)
The need to prioritise food security in the face of a changing climate raises the question of how much agriculture should contribute to global mitigation targets. A global target for reducing methane and nitrous oxide emissions from agriculture of ~1 gigatonne of carbon dioxide equivalent per year (GtCO2e/yr) by 2030 would limit warming in 2100 to 2°C above pre-industrial levels. Yet low emissions development (LED) in agriculture, based on available technologies and policies, will deliver only a portion of the needed mitigation. More transformative options will be needed, including carbon sequestration, reduced food loss and waste, and shifts in consumption.